Nursing Practicum in Gynaecology and Obstetrics – Early Influence Possibilities for a Specialty - Kasch, R.; Baum, P.; Dokter, M.; Zygmunt, M.; Wirkner, J.; Lange, A.; Fröhlich, S.; Merk, H.; Kasch, J. (Geburtshilfe und Frauenheilkunde, 2015)
Background: The shortage of skilled personnel is ubiquitous, basic and further training is a key aspect in the recruitment of new medical colleagues. The significance of the nursing practicum in its function as gateway to the gynaecology and obstetrics discipline is practically unexplored. Methods: In an online questionnaire, medical students in all German faculties were questioned about the practica in their courses. The questionnaire reached 9079 medical students. 149 participants in nursing practica were selectively asked to answer 140 questions. We analysed those students who could, on the basis of their experiences in nursing practica, imagine undertaking an internship (clinical elective) in gynaecology (internship yes “Iy”) separately from those who could not or were still undecided (internship no “In” or, respectively, internship perhaps “Ip”). Results: Altogether 149 medical students who participated in a nursing practicum in the gynaecology discipline were selected, of these 94.9 % were female. 92 (61.7 %) of the students replied that, after their gynaecological nursing practicum, they wanted to undertake an internship in gynaecology (Iy); 39 (26.2 %) answered negatively (In) and 18 (12.1 %) were still undecided (Ip). With regard to the parameters gender, age and duration of study, there were no significant differences among the 3 groups (χ2 0.83). Besides the didactic and professional quality of the training, Iy also mentioned having had a higher practical orientation. They attained their aims more frequently, were better integrated in the health-care team and acquired more practical competences. Satisfaction with the practicum was evaluated as highest among the Iy. Discussion: Those students who could imagine taking an internship in gynaecology were seen to be more satisfied with their practica than those participants who declined or were undecided. The high proportion of females is an early indicator for a feminisation of the specialty. If necessary this could be countered with the help of nursing management.
Keywords: obstetrics; gynaecology; gynaecological nursing practicum; lack of skilled personnel; feminisation; medical students